FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA PEGAWAI PADA BADAN PENGENDALIAN KEPENDUDUKAN DAN KELUARGA BERENCANA DAERAH (BPKKBD) KOTA TERNATE - Djuniarti Djuniarti; Muhammad Asril Arilaha (Jurnal Manajemen Sinergi, 2016)
This study aims to determine the effect of ability, work environment and work discipline  partially or simultaneously to the productivity of employees. The type of research used is quantitative method with total population of employees at the Regional Population Control Board (BPKKBD) Ternate City as many as 118 employees. Sampling technique using proportional random sampling method. 54 employees are designated as research samples. Data analysis technique used multiple regression analysis and data processing technique using SPSS. Where the results of this study indicate that the variables Ability (X1), Work Environment (X2), and Work Discipline (X3) have a positive and significant effect on the productivity of employees at the Regional Population Control Board (BPKKBD) Ternate either partially or simultaneous meaning that Ha  is accepted and H0 is rejected thus the proposed hypothesis is acceptable.  Ability,